Dynamic Interface Formation in Magnetic Thin Film Heterostructures. (23rd November 2018) - Nakashima, Shuhei; Miyamachi, Toshio; Tatetsu, Yasutomi; Takahashi, Yukio; Takagi, Yasumasa; Gohda, Yoshihiro; Yokoyama, Toshihiko; Komori, Fumio
Abstract: Magnetic thin film heterostructures have been widely studied for fundamental interests in the emergence of novel phenomena associated with the heterointerface formation as well as their promising practical potential. Combining X‐ray magnetic circular dichroism with scanning tunneling microscopy, it is shown for fcc Fe thin films grown on Cu(001) with Mn overlayers (Mn/Fe thin film heterostructures) that the interfacial factors dominating the electronic and magnetic properties of the entire system dynamically change with the amount of the Mn overlayer. Element specific magnetization curves of the Fe layer exhibit a two‐step spin reorientation transition from out‐of‐plane to in‐plane direction by increasing the Mn coverage. The atomic‐scale characterizations of structural and electronic properties in combination with the first‐principles calculations successfully unravel the roles of the entangled interfacial factors and clarify the driving forces of the transition. The first step of the transition at a low Mn coverage is dominantly induced by the formation of FeMn disordered alloy at the heterointerface, and the electronic hybridization with the interfacial FeMn ordered alloy is dominant as the origin of the second step of the transition at a high Mn coverage. Abstract : The impacts of interfacial structures on electronic and magnetic properties of Mn/Fe thin film heterostructures are investigated at the atomic scale . The results successfully link the dynamics of the interface FeMn alloy formation to the two‐step spin reorientation transition of the Fe underlayer from out‐of‐plane to in‐plane magnetization with increasing the thickness of the Mn overlayer.